Galvanic Replacement Reaction Involving Core–Shell Magnetic Chains and Orientation‐Tunable Microwave Absorption Properties. Issue 40 (6th September 2020) - Zhao, Biao; Li, Yang; Zeng, Qingwen; Wang, Lei; Ding, Jingjun; Zhang, Rui; Che, Renchao
Abstract: Electromagnetic (EM) wave absorption materials have attracted considerable attention because of EM wave pollution caused by the proliferation of electronic communication devices. One‐dimentional (1D) structural magnetic metals have potential as EM absorption materials. However, fabricating 1D core–shell bimetallic magnetic species is a significant challenge. Herein, 1D core–shell bimetallic magnetic chains are successfully prepared through a modified galvanic replacement reaction under an external magnetic field, which could facilitate the preparation of 1D core–shell noble magnetic chains. By delicately designing the orientation of bimetallic magnetic chains in polyvinylidene fluoride, the composites reveal the decreased complex permittivity and increased permeability compared with random counterparts. Thus, elevated EM wave absorption perfromances including an optimal reflection loss of −43.5 dB and an effective bandwidth of 7.3 GHz could be achieved for the oriented Cu@Co sample. Off‐axis electron holograms indicate that the augmented magnetic coupling and remarkable polarization loss primarily contribute to EM absorption in addition to the antenna effect of the 1D structure to scatter microwaves and ohmic loss of the metallic attribute. This work can serve a guide to construct 1D core–shell bimetallic magnetic nanostructures and design magnetic configuration in polymer to tune EM parameters and strengthen EM absorption properties. Abstract : Herein, core–shell bimetallic magnetic chains which are prepared through a modified galvanic replacement reaction under an external magnetic field, are delicately oriented in PVDF to descend complex permittivity and ascend complex permeability. Furthermore, off‐axis electron holographs are creatively used to investigate polarization loss and magnetic coupling.